A Jewish conductor, a devoted Mahlerite, and a delicate string: The musical life of Heinz Unger, 1895--1965 - Tesler-Mabe, Hernan (University of Ottawa (Canada), 2010)
The orchestral conductor Heinz Unger (1895-1965) was born in Berlin, Germany and was reared from a young age to follow in his father's footsteps and become a lawyer. In 1915, he heard a Munich performance of Gustav Mahler's Das Lied von der Erde conducted by Bruno Walter and thereafter devoted the rest of his life to music and particularly to the dissemination of Gustav Mahler's music. This doctoral dissertation is conceived as a contextual biography that explores the manner in which the strands of German Jewish identity converge and are negotiated by a musician who, as a consequence of persecution, lived a sizeable portion of his life in a Double Diaspora (in the Jewish Diaspora as well as exiled from his European home) yet never cut the ties to a German Jewish tradition informed by the strains of a European cultural heritage. It is a work that discusses the process of Jewish emancipation in Central Europe and in so doing sheds light on the complex issues of ethnicity, "race," nationalism, secularization, and culture and thought as they developed in the modern period and impacted upon Europe and beyond in the first half of the twentieth century. In tracking Heinz Unger's many movements and activities around the world and covering his eventual emigration to Canada, the work simultaneously probes the manner in which European cultural values manifested themselves in disparate parts of the world. It is also a detailed examination of the values that Mahler's oeuvre represents and of one musician's negotiation of these sites of meaning by way of his commitment to Gustav Mahler's music. The first three chapters serve as an extended introduction that in turn surveys Jewish identity in the Diaspora, constructions of Jewish music and their meaning, and the specific cultural significance of Mahler's music in a German Jewish context. The following five chapters are cast as a biography of Heinz Unger (based on the Heinz Unger Fonds at Archives Canada, Ottawa, Ontario) that explores the manner in which the German Jewish musician understood and expressed his dual identity by way of his allegiance to music.
Keywords: Biography.; Music.; History, Modern.; Jewish Studies.